Marcel Broodthaers: “Le Corbeau et le Renard”, un ejercicio fílmico de lectura - Santana Pérez, Sandra (Escritura e Imagen, 2007)
Marcel Broodthaers (Brussels, 1924- Cologne, 1976), poet, sculptor, film maker, author of installations and founder of a fictitious museum, has been one of the most influent and controversial figures in the Art History of the 20th century. This article tries to undertake an analysis of one of his films, “Le Corbeau et Le Renard”, in order to show some of the philosophical and aesthetical implications on the issues of language and artistic subject that are present in the work. The essay of Michel Foucault about the visual works of Rene Magritte can help us to show how images and words articulate their self-referential capacities in the film of the Belgian artist.